ANTIDIABETIC, ANTIHYPERLIPIDEMIC AND RENAL PROTECTIVE ACTIVITIES OF GARCINIA INDICA LINN. CLUSIACEAE (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
To investigate the antidiabetic, antihyperlipidemic and renal protective activities of the aqueous and ethanol extract of Garcinia indica fruit rinds against alloxan induced diabetes in rats. Wistar rats were made diabetic by a single dose of alloxan hydrate [130 mg/kg i.p.]. After the successful induction of experimental diabetes, rats were divided into five groups each comprising a minimum of six rats. The effects of extracts and glibenclamide on fasting blood glucose, plasma lipid levels and renal profile were examined for 21 days. Blood glucose levels and biochemical parameters such as serum cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol, urea and creatinine levels of rats were measured using on weekly intervals i.e day 0, 7, 14 and 21 after daily administration of all extracts at dose of 500 mg/kg. Statistical analysis was performed using Dunnett’s test. p<0.01 was taken as the criterion of significance. Oral administration of both aqueous and ethanol extract for 21 days caused a significant [p<0.01] reduction in blood glucose levels, lipid profile except HDL; urea and creatinine in diabetic rats. Garcinia indica fruit rind possesses antihyperglycemic activity as well improves total lipid levels and renal profile. It can justify folklore uses of the plant in diabetes.